Effect of structural and magnetic disorder on the 3d-5d exchange interactions in La2-xCaxCoIrO6 - Bufaiçal, L.; Sadrollahi, E.; Litterst, F. J.; Rigitano, D.; Granado, E.; Coutrim, L. T.; Araújo, E. B. [UNESP]; Fontes, M. B.; Baggio-Saitovitch, E.; Bittar, E. M. (My University, 2020)
The delicate balance between spin-orbit coupling, Coulomb repulsion, and crystalline electric field interactions observed in Ir-based oxides is usually manifested as exotic magnetic behavior. Here we investigate the evolution of the exchange coupling between Co and Ir for partial La substitution by Ca in La2CoIrO6. A great advantage of the use of Ca2+ as a replacement for La3+ is the similarity of their ionic radii. Thus, the observed magnetic changes can more easily be associated with electronic variations. A thorough investigation of the structural, electronic, and magnetic properties of the La2-xCaxCoIrO6 system was carried out by means of synchrotron x-ray powder diffraction, muon spin rotation and relaxation (μSR), AC and DC magnetization, x-ray absorption spectroscopy (XAS), x-ray magnetic circular dichroism, Raman spectroscopy, electrical resistivity, and dielectric permittivity. Our XAS results show that up to 25% Ca substitution at the La site results in the emergence of Co3+, possibly in a high-spin state, while the introduction of a larger amount of Ca leads to an increase in the Ir valence. The competing magnetic interactions resulting from the mixed valences lead to the coexistence of a magnetically ordered and an emerging spin-glass (SG) state for the doped samples. Our μSR results indicate that for La2CoIrO6 a nearly constant fraction of a paramagnetic (PM) phase persists down to low temperatures, possibly related to the presence of a small amount of Ir3+ and to the antisite disorder at Co/Ir sites. For doped compounds the PM phase freezes below 30 K, but there is still some dynamics associated with the SG. The dielectric data obtained for the parent compound and the one with 25% Ca doping indicate a possible magnetodielectric effect, which is discussed in terms of the electron hopping between the transition-metal ions, the antisite disorder at Co/Ir sites, and the distorted crystalline structure.